Analysing institutional effects in Activity Theory: First steps in the development of a language of description - Daniels, Harry (Outlines. Critical Practice Studies, 2006)
This paper explores the benefits that might arise from an appropriate fusion of the version of Activity Theory being developed by Yrjo Engestrom and the sociology of the late Basil Bernstein. It explores the common roots of the two traditions and on the basis of empirical work carried out in British special schools formulates an approach to the development of a language of description which would extend the analytical power of Activity Theory.